Evaluation of the water quality and auto-purification from the MEIO stream, LEME (SP) - De Sardinha, Diego Souza [UNESP]; Da Conceição, Fabiano Tomazini [UNESP]; De Souza, Antonio Donizetti Gonçalves; Silveira, Alexandre; De Julio, Marcelo; De Gonçalves, Julio César Souza Inácio (My University, 2008)
This investigation utilized hydrochemical relations to evaluate possible anthropogenic inputs at Meio Stream, São Paulo State. Realized three sampling of water during the months of February, April and July/2005, in five samplingpoints analyzing: discharge, temperature, turbidity, pH, electrical conductivity (EC), dissolved oxygen (DO), TDS (total dissolved solids), TSS (total suspended solids), Ca2+, Mg2+, Na+, K+, HCO3-, Ct, SO42; PO43- and NO3-; The characteristics of water close to spring until Leme city allow concluding that there is a small interference in its quality, however the absence of treatment of domestic wastewater at Leme city reduced its quality. It was applied the QUAL 2Kmodeling to evaluate the Meio Stream auto-purification identified the auto-purification zones and indicated the necessity of secondary wastewater treatment, with 76% of efficiency.
Avaliação da qualidade da água e autodepuraç ão do ribeirão do meio, LEME (SP)
Keywords: Anthropogenic influences; Auto-purification mathematical modeling; Environmental management; Water quality